1990
DOI: 10.1148/radiology.175.3.2343133
|View full text |Cite
|
Sign up to set email alerts
|

Disk fragment migration.

Abstract: This report analyzes the most frequently observed migration paths of disk fragments in 47 patients who had extruded or sequestered disks. Observations are based principally on magnetic resonance (MR) images. When disk fragments moved in a superior (42%) or inferior (40%) direction from the donor disk, the displaced disk components were most frequently (94%) dislodged into the right or left half of the anterior epidural space (AES) and rarely straddled the midline. To explain this phenomenon, the authors invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
108
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(112 citation statements)
references
References 0 publications
2
108
0
2
Order By: Relevance
“…Because of the anatomy of the anterior epidural space (AES), most of the sequestrated disc fragment usually migrate in lateral direction in the spinal canal 6,22) . Schelling et al concluded that the migrating path of a disc fragment is determined by the anatomy of the AES, a fairly welldefined space delimited posteriorly by the posterior longitudinal ligament (PLL) and lateral membrane, attached medially to the free edge of the PLL, and stretches laterally to the wall of the spinal canal 21) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the anatomy of the anterior epidural space (AES), most of the sequestrated disc fragment usually migrate in lateral direction in the spinal canal 6,22) . Schelling et al concluded that the migrating path of a disc fragment is determined by the anatomy of the AES, a fairly welldefined space delimited posteriorly by the posterior longitudinal ligament (PLL) and lateral membrane, attached medially to the free edge of the PLL, and stretches laterally to the wall of the spinal canal 21) .…”
Section: Discussionmentioning
confidence: 99%
“…Schelling et al concluded that the migrating path of a disc fragment is determined by the anatomy of the AES, a fairly welldefined space delimited posteriorly by the posterior longitudinal ligament (PLL) and lateral membrane, attached medially to the free edge of the PLL, and stretches laterally to the wall of the spinal canal 21) . Not only these PLL and lateral membrane, but also epidural vessels, fat and nerve roots limit posterior epidural migration of herniated disc fragments 6,13,22) . MRI, especially with gadolinium administration, appears to be the method of choice for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another landmark article, none of the factors were found to influence the direction of migration of the disc fragment in the lumbar canal (9). PEMLIF as quoted in the literature is very rare.…”
Section: Discussionmentioning
confidence: 96%
“…There have been no previous reports of an accurate theory regarding the pathomechanism of the direction of extruded disc material migrating to areas within the cervical spine. According to Schellinger et al [11], the migrating path of a disc fragment is determined by the anatomy of the anterior epidural space. The configuration of the anterior epidural space is identical at the superior and inferior half of a vertebral body.…”
Section: Discussionmentioning
confidence: 99%